Faktor Penyebab Perilaku Membolos Siswa dan Implikasinya terhadap Layanan Bimbingan dan Konseling - Syakura, Muhammad Abdan; Neviyarni, Neviyarni (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
Truancy is a form of disciplinary violation that can negatively impact students’ academic achievement and character development. This study aims to identify the factors contributing to truancy among junior high school students and to analyze its implications for school guidance and counseling services. A quantitative descriptive approach was employed, involving 20 purposively selected students from SMPN 2 Batang Anai. Data were collected using a questionnaire covering both internal and external factors. The results indicate that dominant internal factors include a desire to play and lack of learning motivation (60%), while key external factors are peer influence and insufficient teacher supervision (70%). These findings reveal that truancy behavior arises from a combination of personal and environmental factors. Accordingly, comprehensive, and responsive guidance and counseling services, such as information services, group counseling, and parent-school collaboration are essential to prevent and address truancy in a structured manner.